2018
DOI: 10.3390/f10010007
|View full text |Cite
|
Sign up to set email alerts
|

The Relic Trochodendron aralioides Siebold & Zucc. (Trochodendraceae) in Taiwan: Ensemble Distribution Modeling and Climate Change Impacts

Abstract: Trochodendron aralioides Siebold & Zuccarini (Trochodendraceae) is a famous relic tree species. Understanding the comprehensive spatial distribution and likely impacts of climate change on T. aralioides in its main habitat—Taiwan—is of great importance. We collected occurrence data and bioclimatic data to predict the current and future (year 2050) distribution by ensemble distribution modeling on the BIOMOD2 platform. Visualization of occurrence point data revealed that the main population of T. aralioides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…For each species, we used ten modeling algorithms embedded in the biomod2 package: generalized linear models (GLM), boosted regression trees (GBM), generalized additive model (GAM), classification tree analysis (CTA), artificial neural network (ANN), surface range envelop or BIOCLIM (SRE), flexible discriminant analysis (FDA), multiple adaptive regression splines (MARS), random forests (RF), and maximum entropy (MaxEnt). These algorithms were chosen because they have shown good ability to predict current species distribution and have been widely used in ecological modeling (Hamid et al, ; Lin & Chiu, ; Thuiller, ). Combining the predictions of individual algorithms to make ensemble prediction provides results that are more robust and also enables the assessment of the uncertainty generated from the modeling procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each species, we used ten modeling algorithms embedded in the biomod2 package: generalized linear models (GLM), boosted regression trees (GBM), generalized additive model (GAM), classification tree analysis (CTA), artificial neural network (ANN), surface range envelop or BIOCLIM (SRE), flexible discriminant analysis (FDA), multiple adaptive regression splines (MARS), random forests (RF), and maximum entropy (MaxEnt). These algorithms were chosen because they have shown good ability to predict current species distribution and have been widely used in ecological modeling (Hamid et al, ; Lin & Chiu, ; Thuiller, ). Combining the predictions of individual algorithms to make ensemble prediction provides results that are more robust and also enables the assessment of the uncertainty generated from the modeling procedure.…”
Section: Methodsmentioning
confidence: 99%
“…For each species, we used ten modeling The standard deviation from the mean AUC of all models (10 modeling algorithms × 10 replicates). good ability to predict current species distribution and have been widely used in ecological modeling (Hamid et al, 2019;Lin & Chiu, 2019;Thuiller, 2003). Combining the predictions of individual algorithms to make ensemble prediction provides results that are more robust and also enables the assessment of the uncertainty generated from the modeling procedure.…”
Section: Calibration and Evaluation Of Species Distribution Modelsmentioning
confidence: 99%
“…Its presence is subject to strong pressures, both from harvesting and land-use change and the effect of climate change. Given this risky scenario for these populations, it is important to know the potential distribution; for this purpose, the use of modeling based on environmental variables is a useful tool, because changes have an impact on biotic interactions (Lin & Chiu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…sinense showed habitat loss in low‐altitude areas under future climate warming, and this scenario is consistent with a previous study on Tr. aralioides (Lin & Chiu, 2019), which indicated that the central Taiwanese population will migrate upward and the northern Taiwanese population could lose most of its current habitats. Low‐altitude regions are therefore critical for the future conservation of both species.…”
Section: Discussionmentioning
confidence: 99%